2022
DOI: 10.3390/s22208013
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nitrogen Content Detection Based on Near-Infrared Spectroscopy

Abstract: Traditional soil nitrogen detection methods have the characteristics of being time-consuming and having an environmental pollution effect. We urgently need a rapid, easy-to-operate, and non-polluting soil nitrogen detection technology. In order to quickly measure the nitrogen content in soil, a new method for detecting the nitrogen content in soil is presented by using a near-infrared spectrum technique and random forest regression (RF). Firstly, the experiment took the soil by the Xunsi River in the area of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…At the same time, the correct model and processing method need to be used, making prediction difficult. For the modeling methods, the overall ranking of model performance is as follows: RF > BPNN > SVM > PLSR, which is consistent with the findings of previous studies, but the order of XGBoost is usually not fixed [37,45,52,53]. The prediction of different soil parameters is different for different data preprocessing methods and modeling approaches.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…At the same time, the correct model and processing method need to be used, making prediction difficult. For the modeling methods, the overall ranking of model performance is as follows: RF > BPNN > SVM > PLSR, which is consistent with the findings of previous studies, but the order of XGBoost is usually not fixed [37,45,52,53]. The prediction of different soil parameters is different for different data preprocessing methods and modeling approaches.…”
Section: Discussionsupporting
confidence: 82%
“…Kawamura et al [35,44] found that the machine learning model showed higher accuracy than the traditional linear model (e.g., multiple linear stepwise regression and partial least squares) when predicting soil parameters (e.g., N and P) using Vis-NIR. Previous research in their study on predicting soil TN using Vis-NIR technology combined with support vector machines, random forests, extreme gradient boosting (XGBoost), and backpropagation neural networks discovered that all machine learning methods could achieve accurate TN predictions, with the model accuracy ranking as follows: RF > BPNN > SVM [37,45,52,53]. XGBoost's performance may be higher or somewhere in between.…”
Section: Introductionmentioning
confidence: 99%
“…But in EMEs and similar contexts, ML also offers another complementary tool: data streams which are either difficult to capture or process (Nair et al, 2023) can be gap filled or interpreted with higher confidence and representativeness. Further development of techniques currently only possible at laboratory or homogenous agricultural scale may allow dynamic sub annual time series of difficult to measure parameters such as photosynthetic capacity (Heckmann et al, 2017), nutrient pools both in biomass and available in soil (Tan et al, 2022), or phenological dynamics beyond leaves, especially those belowground (Wang et al, 2022). This is particularly relevant belowground, where data are particularly sparse.…”
Section: New Data For Eme-model Synthesismentioning
confidence: 99%
“…Because the working voltage of different modules of the lower computer is different, and the battery voltage is 12 V, it is necessary to design a voltage-stabilizing circuit based on the LM2596S chip to convert 12 V voltage into 5 V voltage, so that the main controller can work normally. The voltage-stabilizing circuit based on the AMS1117 chip is designed to convert 5 V to 3.3 V, so that the communication module can work normally [22].…”
Section: Power Supply Module Designmentioning
confidence: 99%